Pancasila as the basis of the Ahlusunnah Wal-Jamaah Islamic Perspective - Agung Aryadi Putra; Jaenal Abidin; Ferianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Pancasila, as the basis of the Indonesian state, has five precepts that function as the ideological and philosophical basis of the state. From the perspective of Islam Ahlussunnah wal-Jama'ah, discussions about Pancasila can focus on how the values in Pancasila are in harmony with Islamic principles. The background regarding Pancasila as the basis of the state from the perspective of Islam Ahlussunnah wal Jamaah (Aswaja) is based on several important historical and theological factors, apart from that, Pancasila as the basis of the Indonesian state has a harmonious relationship with Islam, especially from the perspective of Ahlussunnah wal Jamaah (Aswaja). Nahdlatul Ulama (NU), as the main representation of Aswaja in Indonesia, has expressed a positive attitude and supports Pancasila as the basis of the state. Muhammad Mahfud MD in the introduction to the book Constitutional Sharia in an Islamic Perspective by Masdar Farid Mas'udi explains that Indonesia, based on Pancasila and the 1945 Constitution, is an Islamic country, but not an Islamic country. The Islamic state referred to by Mahfud is a country that does not officially use Islamic names and symbols, but whose subtansions contain Islamic teaching values. Such as leadership that is fair, trustworthy, domocratic, respects human rights and so on. Pancasila from the perspective of Islam Ahlussunnah wal Jamaah (Aswaja) can be understood as values that are in harmony with Islamic teachings adhered to by the majority of Muslims in Indonesia. Aswaja emphasizes moderation, tolerance and balance in religion and in social life.